Hybrid Experiments in Higher Education: General Trends and Local Factors at the Academic–Business Boundary. (May 2018) - Kleinman, Daniel Lee; Feinstein, Noah Weeth; Downey, Greg; Peterson, Sigrid; Fukada, Chisato
In response to the many pressures facing public higher education, public universities are experimenting with business-oriented practices that seem likely to alter their nature and purposes. In this paper, we examine several hybrid experiments—new organizational strategies intended deliberately, sometimes explicitly, to hybridize the traditional norms and practices associated with academia and business at one emblematic public university. These cases illustrate how each hybrid experiment is a tacit response to existing norms and strategies that govern the university–business boundary, initiated as a hedge against the challenging fiscal and political climate. Taken together, they do not lead to a unitary and/or linear spread of business codes and practices. Instead, what some have referred to as "business logic" appears multifaceted, having many elements that are deployed, institutionalized, and perceived differently in different contexts, even within a single university.